1999
DOI: 10.1111/j.1541-1338.1999.tb00847.x
|View full text |Cite
|
Sign up to set email alerts
|

The Policy Termination Process

Abstract: 0The purposes of this article are twofold. First, f r o m a review of the extant literature on termination of policies, programs, and organizations, we identij) the "crucial variables '' that are believed to affect termination. In doing so, we develop a descriptive model of program termination. Then, we utilize this model as a hueristic device to examine the termination of federal revenue-sharing programs in 1986. After reviewing the available literature on this topic and analyzing the case of revenue-sharing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 21 publications
6
38
0
2
Order By: Relevance
“…These political contests can occur at any level of government, and presumably, the institutions if not the nature of the process varies by decision‐making arena. Most of the empirical work in policy termination has focused on the termination of federal policies, programs, and organizations (e.g., Frantz, 1997, 2002; Kaufman, 1976; Kirkpatrick, Lester, & Peterson, 1999; Lewis, 2002). Our interest is in local termination decisions, and these have not been widely studied.…”
Section: Model Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…These political contests can occur at any level of government, and presumably, the institutions if not the nature of the process varies by decision‐making arena. Most of the empirical work in policy termination has focused on the termination of federal policies, programs, and organizations (e.g., Frantz, 1997, 2002; Kaufman, 1976; Kirkpatrick, Lester, & Peterson, 1999; Lewis, 2002). Our interest is in local termination decisions, and these have not been widely studied.…”
Section: Model Developmentmentioning
confidence: 99%
“…Since public programs are supported with a government budget, it is reasonable to assert that budget deficits could force the termination of certain programs. Moreover, there is some empirical support for the role of budget deficits (e.g., Kirkpatrick et al., 1999). This suggests that cost savings are the motivation for some terminations.…”
Section: Model Developmentmentioning
confidence: 99%
“…Kaufmann collected data on the number of organizations existing in 1923 and 1 E.g. the article by Robert Behn "How to Terminate a Public Policy: A Dozen Hints for a Would-be Terminater" (Behn 1978) and the conceptual framework by Kirkpatrick et al (1999). compared it with the organizations still "alive" in 1973. He found that 27 organizations had indeed been terminated, while during the same period 294 new organizations had been established.…”
Section: Introductionmentioning
confidence: 99%
“…¿Cuáles de las variables a las que nos hemos referido en las páginas anteriores pueden aplicarse al caso que presentamos? Fuente: elaboración propia a partir de las aportaciones de Kirkpatrick et al, (1999), DeLeon (1978aDeLeon ( y 1987, Bothum y Comer (1979) y Bardach (1976).…”
Section: El Estudio De La Terminación De Las Políticas Públicasunclassified